Diaheliotropic leaf movement enhances leaf photosynthetic capacity and photosynthetic light and nitrogen use efficiency via optimising nitrogen partitioning among photosynthetic components in cotton (Gossypium hirsutum L.). (7th January 2018) - Yao, H.; Zhang, Y.; Yi, X.; Zhang, X.; Fan, D.; Chow, W. S.; Zhang, W.
Abstract: Phototropic leaf movement of plants is an effective mechanism for adapting to light conditions. Light is the major driver of plant photosynthesis. Leaf N is also an important limiting factor on leaf photosynthetic potential. Cotton ( Gossypium hirsutum L.) exhibits diaheliotropic leaf movement. Here, we compared the long‐term photosynthetic acclimation of fixed leaves (restrained) and free leaves (allowed free movement) in cotton. The fixed leaves and free leaves were used for determination of PAR, leaf chlorophyll concentration, leaf N content and leaf gas exchange. The measurements were conducted under clear sky conditions at 0, 7, 15 and 30 days after treatment (DAT). The results showed that leaf N allocation and partitioning among different components of the photosynthetic apparatus were significantly affected by diaheliotropic leaf movement. Diaheliotropic leaf movement significantly increased light interception per unit leaf area, which in turn affected leaf mass per area (LMA), leaf N content ( N A ) and leaf N allocation to photosynthesis ( N P ). In addition, cotton leaves optimised leaf N allocation to the photosynthetic apparatus by adjusting leaf mass per area and N A in response to optimal light interception. In the presence of diaheliotropic leaf movement, cotton leaves optimised their structural tissue and photosynthetic characteristics, such as LMA, N A and leaf N allocation to photosynthesis, so that leaf photosynthetic capacity was maximised to improve the photosynthetic use efficiency of light and N under high light conditions.